An investigation and evaluation of cross-border truck transportation from Mae Sot-Myawaddy to Yangon - Kesinee Saowadee (2018)
© ExcelingTech Pub, UK. This study investigates both direct and indirect factors that affected to cross-border truck transportation from Mae Sot-Myawady to Yangon. The study used 200 respondents for collecting data, employed the SEM model and used Confirmatory Factor Analysis (CFA) to figure out factors loading. From the result, it found that the reliability of transportation service provider was the most important factor, which effected to cross-border truck transportation; the factor loading was equal to 0.92. Even though, traders and transport participants who used Mae Sot-Myawaddy to Yangon route concerned other related factors due to instability and minority conflicts in Myanmar, this study could be a potential advantageous guideline for forming competitive advantages and strategy development of using crossborder truck transportation.